2019
DOI: 10.1038/s41598-019-54258-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of hESC- and iPSC-derived lentoid bodies

Abstract: The ocular lens serves as an excellent system to investigate the intricate details of development and differentiation. Generation of lentoid bodies or lens-like structures using pluripotent stem cells is important for understanding the processes critical for lens morphogenesis and the mechanism of cataractogenesis. We previously reported the generation of peripheral blood mononuclear cell (PBMC)-originated, induced pluripotent stem cells (iPSCs). Here, we report generation of lentoid bodies from human embryoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…This method significantly increased the induction efficiency and volume of the lentoid body (diameter approximately 3 mm). Further transcriptional analysis confirmed that the expression profiles of both the hESC-and hiPSC-derived lentoid bodies generated with the "fried egg" protocol were comparable (Ali et al, 2019) and mimicked the early stage of lens development (Ali et al, 2020). Nevertheless, the "fried egg" method may be regarded as an upgrade of the three-stage protocol, as the induction time window and induction supplement are relatively identical.…”
Section: Future Directionsmentioning
confidence: 69%
“…This method significantly increased the induction efficiency and volume of the lentoid body (diameter approximately 3 mm). Further transcriptional analysis confirmed that the expression profiles of both the hESC-and hiPSC-derived lentoid bodies generated with the "fried egg" protocol were comparable (Ali et al, 2019) and mimicked the early stage of lens development (Ali et al, 2020). Nevertheless, the "fried egg" method may be regarded as an upgrade of the three-stage protocol, as the induction time window and induction supplement are relatively identical.…”
Section: Future Directionsmentioning
confidence: 69%
“…The LBs generated using our method not only expressed various human lens-specific markers during each stage of differentiation, but also exhibited a lens-like structure and optic properties that resemble to a large extent those seen in human-lens development in morphological, molecular, and structural aspects. Recent studies confirmed highly overlapping transcriptomic and proteomic profiles of LBs derived from human iPSCs via the “fried egg” method and murine lens epithelial and fiber cells 14 , 15 . In addition, these studies observed closely packed lens epithelial and differentiating fiber-like cells in iPSC-derived LBs, which showed a similar ultrastructure to that of the lens 14 , 15 .…”
Section: Introductionmentioning
confidence: 70%
“…Recent studies confirmed highly overlapping transcriptomic and proteomic profiles of LBs derived from human iPSCs via the “fried egg” method and murine lens epithelial and fiber cells 14 , 15 . In addition, these studies observed closely packed lens epithelial and differentiating fiber-like cells in iPSC-derived LBs, which showed a similar ultrastructure to that of the lens 14 , 15 . Therefore, the availability of LBs provides an opportunity to generate cataract-disease models from individual-specific iPSCs.…”
Section: Introductionmentioning
confidence: 70%
“…The common ectodermal origin of the eye retina, iris, and lens probably explains the cases of formation of lentoids, the lens-like structures synthesizing crystallins, in tissue cultures from the retina and iris of birds [ 66 ] and rodents [ 67 ] ( Figure 2 ). Currently, lentoid bodies expressing crystallins are obtained from human embryonic (hESC) and induced human (iPSC) stem cells [ 68 , 69 ]. An ultrastructure analysis of hESC- and iPSC-derived lentoid bodies has identified closely packed lens epithelial and differentiating fiber cells.…”
Section: Cell-type Conversion Of Iris Pigment Epithelial (Ipe) Cellsmentioning
confidence: 99%
“…An ultrastructure analysis of hESC- and iPSC-derived lentoid bodies has identified closely packed lens epithelial and differentiating fiber cells. A comparison of the mouse lens epithelial and fiber cell transcriptomes with hESC- and iPSC-derived lentoid body transcriptomes has shown a more then 96% overlap [ 69 ].…”
Section: Cell-type Conversion Of Iris Pigment Epithelial (Ipe) Cellsmentioning
confidence: 99%